Constitutive activation of NF-κB inducing kinase (NIK) in the mesenchymal lineage using Osterix (Sp7)- or Fibroblast-specific protein 1 (S100a4)-Cre drives spontaneous soft tissue sarcoma. - Jennifer L Davis; Roman Thaler; Linda Cox; Biancamaria Ricci; Heather M Zannit; Fei Wan; Roberta Faccio; Amel Dudakovic; Andre J van Wijnen; Deborah J Veis (PLoS ONE, 2021)
Aberrant NF-κB signaling fuels tumor growth in multiple human cancer types including both hematologic and solid malignancies. Chronic elevated alternative NF-κB signaling can be modeled in transgenic mice upon activation of a conditional NF-κB-inducing kinase (NIK) allele lacking the regulatory TRAF3 binding domain (NT3). Here, we report that expression of NT3 in the mesenchymal lineage with Osterix (Osx/Sp7)-Cre or Fibroblast-Specific Protein 1 (FSP1)-Cre caused subcutaneous, soft tissue tumors. These tumors displayed significantly shorter latency and a greater multiple incidence rate in Fsp1-Cre;NT3 compared to Osx-Cre;NT3 mice, regardless of sex. Histological assessment revealed poorly differentiated solid tumors with some spindled patterns, as well as robust RelB immunostaining, confirming activation of alternative NF-κB. Even though NT3 expression also occurs in the osteolineage in Osx-Cre;NT3 mice, we observed no bony lesions. The staining profiles and pattern of Cre expression in the two lines pointed to a mesenchymal tumor origin. Immunohistochemistry revealed that these tumors stain strongly for alpha-smooth muscle actin (αSMA), although vimentin staining was uniform only in Osx-Cre;NT3 tumors. Negative CD45 and S100 immunostains precluded hematopoietic and melanocytic origins, respectively, while positive staining for cytokeratin 19 (CK19), typically associated with epithelia, was found in subpopulations of both tumors. Principal component, differential expression, and gene ontology analyses revealed that NT3 tumors are distinct from normal mesenchymal tissues and are enriched for NF-κB related biological processes. We conclude that constitutive activation of the alternative NF-κB pathway in the mesenchymal lineage drives spontaneous sarcoma and provides a novel mouse model for NF-κB related sarcomas.